Formation Of Iron Oxides Under Varying Condition Of Ph, Temperature And Neutralization Dosage - Sharipudin, Mohamad Nazmie Mohd (Universiti Sains Malaysia, 2017)
Recently, schwertmannite, a ferric oxyhydroxy sulfate mineral, has attracted attention broadly due to its high sorption capacity for toxic arsenic species. This research work has been carried out on the synthesis and characterization of schwertmannite. The present study involved the synthesis of schwertmannite at varying condition such as speed of agitation, final pH, temperature and neutralization dosage. The parameters that has been used in this research work are speed of agitation (250 rpm and 350 rpm), final pH (<3.5 and >3.5), temperature (25°C and 60°C) and neutralization dosage (1000 μL and 2000 μL). The synthesized schwertmannite was obtained using modified neutralization method. This research work involved preliminary trial runs using the neutralization method and also modification that have been carried out. In the synthesis using the neutralization method, about 500 mL of 0.05 M